Transformation of regional system of rural settlement of Zaporizhia region in the post-soviet period - Kseniia Nelipa (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
As a result of strengthening of globalization and transition ofUkraineto the market economy the regional settlement system have changed. Considerable changes were tested by the network of rural settlements of industrial regions, such as the Zaporizhia region. Therefore determination of modern tendencies and problems of functioning of the regional systems of rural settlement of this area became a necessity.